Tobacco treatment incorporating contingency management, nicotine replacement therapy, and behavioral counseling for pregnant women who use substances: a feasibility trial - Jackson, Melissa A.; Brown, Amanda L.; Baker, Amanda L.; Bonevski, Billie; Haber, Paul; Bonomo, Yvonne; Blandthorn, Julie; Attia, John; Perry, Natasha; Barker, Daniel; Gould, Gillian S.; Dunlop, Adrian J. (Frontiers in Psychiatry, 2023)
Introduction Most pregnant women with substance use problems smoke, and few will quit during their pregnancy. Tobacco treatment is often overlooked, with the focus usually placed on other substance use. Additionally, few targeted effective treatments for this group exist. To address this, the feasibility of an intensive tobacco treatment incorporating contingency management (CM) that featured non–face-to-face delivery was examined. Methods A single-arm pre-post design feasibility trial was conducted in three antenatal services that support women who use substances in metropolitan Australia. Participants were over the age of 15, had <33-week gestation, and smoked tobacco daily. They received financial incentives for daily carbon monoxide-verified smoking abstinence or reduction through an internet-based CM programme, nicotine replacement therapy (NRT) posted to women and partners or household members who smoked and telephone-delivered behavioral counseling from study enrolment to birth. Results Of the 101 referrals, 46 women (46%) consented. The mean (SD) age was 31(±6) years, and the gestation period was 22(±6) weeks. Nineteen (41%) of those enrolled were retained for 12-week postpartum. Of 46 women, 32 (70%) utilized CM; 32 (70%) used NRT for ≥2 weeks; 23 (50%) attended ≥1 counseling session; and 15 (22%) received NRT for partners/household members. Fifteen (33%) were verified abstinent from tobacco at delivery after a median (IQR) period of abstinence of 65(36–128) days. All non-smokers at birth utilized NRT and financial incentives, and 9/15 (60%) utilized counseling. Four (9%) were abstinent at 12-week postpartum. Median cigarettes smoked/day reduced from baseline to delivery (10(6–20) to 1(0-6) p =< 0.001). Women who quit smoking had more education (72% vs. 33% p =< 0.02), completed more CO samples (median (IQR) 101(59–157) vs. 2(0–20) p =< 0.001), and received more incentives (median (IQR) $909($225–$1980) vs. $34($3–$64) p =< 0.001). Intervention acceptability was rated favorably by participants (9 items rated 0–10 with scores >5 considered favorable). Discussion This study demonstrated the feasibility and acceptability of a consumer-informed, non–face-to-face intensive tobacco treatment, highlighting the potential of remotely delivered technology-based CM to reduce the health impact of tobacco smoking in high-priority populations. The intervention demonstrates scale-up potential. Future studies should extend treatment into the postpartum period, utilizing new technologies to enhance CM delivery and improve counseling provision and partner support. Clinical trial registration https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=374196, ACTRN1261800056224.